Osseous suprascapular canal: rare variant that would hinder suprascapular nerve block and posterior surgical approach - Al-Redouan, Azzat; Salavova, Sarka; Cvrček, Jan; Velemínská, Jana; Velemínský, Petr; Kachlik, David (Surgical and radiologic anatomy, 2022)
PURPOSE: To report atypical anatomical variation of an osseous suprascapular canal, and to elaborate on its clinical significance as a potential anatomical factor that could obscure a direct posterior surgical approach and suprascapular nerve block. METHODS: Osteological observational study of the scapula with emphasis on the suprascapular space. The pool of investigated sample size was collectively 768 specimens composed of 529 adult dry scapulae (240 paired, 289 un-paired), 54 children dry scapulae, 135 wet scapulae observed during cadaveric dissections, 47 retrospective 3D CT reconstructions, and 3 retrospective full sequence shoulder MRI. The two reported cases came from the 240 (120 skeleton) observed paired scapulae. Furthermore, the osseous suprascapular canal was examined by X-rays and its internal path was exposed by CT sections. A narrative review was conducted to investigate any relevant reports on the subject matter. RESULTS: Two left dry bone scapulae with unilateral osseous suprascapular canal were found. The incidence of this atypical morphology of an osseous canal is probably five cases reported in three studies including this cases study. CONCLUSIONS: The reported cases aid in explaining additional possible anatomical factors that could lead to below threshold anesthetic effect in posterior suprascapular nerve block procedures. Therefore, it is more practical to visualize the suprascapular canal by some imaging method before attempting to blindly access the suprascapular nerve in nerve block or posterior surgical approach due to the rare potential existence of an ossified barrier hindering the procedure. LEVEL OF EVIDENCE: V Basic Science Research.
Keywords: Suprascapular nerve; dospělí; Scapula; Shoulder; dítě; Nerve Compression Syndromes; Nerve Block; Adult; Posterior surgical approach; lidé; Suprascapular canal; Suprascapular nerve entrapment; nervová blokáda; lopatka; Nerve block; retrospektivní studie; úžinové syndromy; pozorovací studie jako téma; Observational Studies as Topic; rameno; Suprascapular notch; Child; Retrospective Studies; Humans